Rancang Bangun Aplikasi Kamus Bahasa Arab-Indonesia Berbasis Android untuk Pembelajaran di Lingkungan Pesantren El-Bayan - ferdian, mohammad (Jurnal Teknologi dan Bisnis, 2022)
The dictionary is a tool in the form of a book that contains words or meanings used to translate a language. In general, dictionaries are arranged alphabetically along with a description of their meaning, usage, or translation. Likewise with the Arabic Latin Indonesian dictionary which is very necessary in translating the meaning of the Arabic word. So that it makes it easier for translators to find the meaning of Indonesian Latin Arabic words without having to look for translations with words written in Arabic. For this reason, an application is needed that can assist users in translating a language that is easy to carry and can be used anytime and anywhere. The application is an android application that can be installed on a mobile phone. The Latin Arabic dictionary application requires a search process that supports the performance of the application so that the search process can shorten the search time itself. In this study, the boyer-moore algorithm is a string search algorithm that has the fastest search, because matched strings move from right to left, so that it can shorten time and simplify the use of Indonesian Arabic Latin dictionary applications. This Arabic Latin Indonesian dictionary application is designed based on Android using the Java programming language.